Development of physics learning tools based on inquiry to increase creative thinking skills. Issue 1 (February 2021) - Asy'ari, M; Prayogi, S; Mirawati, B; Syarifuddin,; Hunaepi,; Syahrir,; Suhirman,
Abstract: This study aimed to produce physics learning tools based on inquiry that are valid, practical, and effective to improve students' creative thinking skills on heat material. This study is a developmental research using the 4D (define, design, develop, disseminate) model. Learning tools in the form of syllabus, lesson plan, student activity sheets, student textbooks, and test instruments were validated by 2 experts before being implemented on 22 students. The research data were collected using instruments of validation, observation, questionnaires, and tests which were then analyzed descriptively and statistically. The results showed that the learning tools produced was valid in terms of content and construct, was practical based on the implementation of learning and student responses, and was effective in improving students' creative thinking skills. Research findings based on indicators of creative thinking skills such as fluency, flexibility, originality, and elaboration are also described in this paper.